2019
DOI: 10.1038/s41564-019-0416-7
|View full text |Cite
|
Sign up to set email alerts
|

Viral complementation of immunodeficiency confers protection against enteric pathogens via interferon-λ

Abstract: Commensal microbes profoundly impact host immunity to enteric viral infections 1 . We have shown that the bacterial microbiota and host antiviral cytokine interferon-lambda (IFN-λ) determine the persistence of murine norovirus in the gut 2 , 3 . However, the effects of the virome in modulating enteric infections remain unexplored. Here we report that murine astrovirus can complement primary immunodeficiency to protect against muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 47 publications
4
82
0
Order By: Relevance
“…Enteric bacteria counteract the Type III IFN response, enabling the establishment of persistent infection [29]. Interestingly, the induction of Type III IFN by murine astrovirus can provide protection against MNoV [43], indicating that the interplay between viruses and microbiota extends beyond bacteria.…”
Section: Modulation Of Innate and Adaptive Immune Responses By The MImentioning
confidence: 99%
“…Enteric bacteria counteract the Type III IFN response, enabling the establishment of persistent infection [29]. Interestingly, the induction of Type III IFN by murine astrovirus can provide protection against MNoV [43], indicating that the interplay between viruses and microbiota extends beyond bacteria.…”
Section: Modulation Of Innate and Adaptive Immune Responses By The MImentioning
confidence: 99%
“…This response is shared with AstV in other species. For example, murine AstV infection induces IFN-λ in intestinal epithelial cells, which depending on the mouse background, can protect the animals from subsequent murine norovirus or murine rotavirus infection [62]. Interestingly, while this response is shared with influenza virus, a respiratory virus, which also induces both type I and III IFNs in primary lung epithelial cells [63,64], it is different from rotavirus, which upregulated only type III, but not type I IFNs, in HIE [65,66].…”
Section: Fig 8 Pharmacological Blockage Of Endogenous Ifn Response Imentioning
confidence: 99%
“…Figure 367 12). A recent study has shown that production of a type III interferon mediated 368 antiviral immune response in mice was key to protect them from subsequent 369 enteric virus infections (Ingle et al, 2019). This suggests that production of type 370 III IFN against enteric viruses is key to protecting the gut against further 371 challenges.…”
mentioning
confidence: 99%